Determinants of Insufficient Knowledge About Multidrug-Resistant Tuberculosis Among Tuberculosis Patients in Kinshasa, Democratic Republic of the Congo: A Cross-Sectional Study. - Jacques Nkolangi Bakokela; Gérard Eloko Eya Matangelo; Bob Senker Ndimba; Emmanuel Kitete Mulongo; Mbadu Zebe; Jean-Paul Ngbolua Koto-Te-Nyiwa; Jules Kangite Moti (Student's Journal of Health Research Africa, 2026)
Background: Multidrug-resistant tuberculosis (MDR-TB) remains an important public health challenge, particularly in settings with a high tuberculosis burden. This study aimed to identify factors associated with insufficient knowledge about MDR-TB among tuberculosis patients receiving care in Kinshasa, Democratic Republic of the Congo (DRC). Methods: A quantitative analytical cross-sectional study was conducted among 165 tuberculosis patients aged ≥15 years receiving care at selected tuberculosis diagnosis and treatment facilities in Kinshasa. Data were collected using a structured questionnaire assessing knowledge of MDR-TB, sociodemographic characteristics, access to health information, and selected sociocultural factors. Knowledge was categorized as insufficient when the participant obtained